The Cholinergic Anti-Inflammatory Pathway as a Conceptual Framework to Treat Inflammation-Mediated Renal Injury - Jonas Jarczyk; Benito A. Yard; Simone Hoeger (Karger Publishers, 2019)
Background: The cholinergic anti-inflammatory pathway, positioned at the interface of the nervous and immune systems, is the efferent limb of the "inflammatory reflex" which mainly signals through the vagus nerve. As such, the brain can modulate peripheral inflammatory responses by the activation of vagal efferent fibers. Importantly, immune cells in the spleen express most cholinergic system components such as acetylcholine (ACh), choline acetyltransferase, acetylcholinesterase, and both muscarinic and nicotinic ACh receptors, making communication between both systems possible. In general, this communication down-regulates the inflammation, achieved through different mechanisms and depending on the cells involved. Summary: With the awareness that the cholinergic anti-inflammatory pathway serves to prevent or limit inflammation in peripheral organs, vagus nerve stimulation has become a promising strategy in the treatment of several inflammatory conditions. Both pharmacological and non-pharmacological methods have been used in many studies to limit organ injury as a consequence of inflammation. Key Messages: In this review, we will highlight our current knowledge of the cholinergic anti-inflammatory pathway, with emphasis on its potential clinical use in the treatment of inflammation-triggered kidney injury.